Diagnostic cut-off values and grading of carpal tunnel syndrome by shear wave elastography at different tunnel locations correlated with gold standard nerve conduction study – a case-control study - Bhalke Prashat; Pattath Sankaran Priya; Prabhu Arvind N.; Kadavigere Rajagopal; Koteshwara Prakashini (Journal of Ultrasonography)
The gold standard nerve conduction study for diagnosing carpal tunnel syndrome is often painful and has variable diagnostic accuracy. This study aimed to evaluate the diagnostic performance of shear wave elastography in correlation with nerve conduction study.